Performance of solid oxide fuel cell with gradient-structured thin-film cathode composed of pulsed-laser-deposited lanthanum strontium manganite-yttria-stabilized zirconia composite - Myung, D.-H.; Hong, J.; Hwang, J.; Lee, J.-H.; Lee, H.-W.; Kim, B.-K.; Cho, S.-G.; Son, J.-W. (Korean Ceramic Society, 2011)
The effect of the application of lanthanum strontrium manganite and yttria-stabilized zirconia (LSM-YSZ) nano-composite fabricated by pulsed laser deposition (PLD) as a cathode of solid oxide fuel cell (SOFC) is studied. A gradient-structure thin-film cathode composed of 1 micron-thick LSM-YSZ deposited at an ambient pressure (Pamb) of 200 mTorr; 2 micron-thick LSM-YSZ deposited at a Pamb of 300 mTorr; and 2 micron-thick lanthanum strontium cobaltite (LSC) current collecting layer was fabricated on an anode-supported SOFC with an ∼8 micron-thick YSZ electrolyte. In comparison with a 1 micron-thick nano-structure single-phase LSM cathode fabricated by PLD, it was obviously effective to increase triple phase boundaries (TPB) over the whole thickness of the cathode layer by employing the composite and increasing the physical thickness of the cathode. Both polarization and ohmic resistances of the cell were significantly reduced and the power output of the cell was improved by a factor of 1.6.
Keywords: Cathodes; Electrolytes; Lanthanum; Manganites; Nanocomposite films; Nanocomposites; Nanostructures; Ohmic contacts; Pulsed laser deposition; Pulsed lasers; Strontium; Thin films; Yttria stabilized zirconia; Yttrium oxide; Zirconia; Ambient pressures; Anode-supported SOFCs; Gradient structure; Lanthanum strontium cobaltites; Lanthanum strontium manganite; Physical thickness; Thin film cathodes; Triple phase boundary; Solid oxide fuel cells (SOFC)